A novel system for rapid conversion of Gardner embryo grades to linear scale numeric variables. Issue 5 (May 2023) - Pierson, Hannah E.; Invik, Jesse; Meriano, Jim; Pierson, Roger A.
Abstract: Research question: Can Gardner embryo grades be converted to numeric interval variables to improve the incorporation of embryo grading in statistical analyses? Design: An equation that can be used to convert Gardner embryo grades to regular interval scale variables was developed: the numerical embryo quality scoring index (NEQsi). The NEQsi system was then validated with a retrospective chart analysis assessing IVF cycles ( n = 1711) conducted at a single Canadian fertility centre between 2014 and 2022. Gardner embryo grades on file were assigned using EmbryoScope and converted to NEQsi scores. Descriptive statistics, univariate logistic regressions and generalized estimating equations with cycle outcomes were prepared to demonstrate the relationship between NEQsi score and probability of pregnancy. Results: NEQsi produces interval numerical scores that range from 2 to 11. Patient case files in which single embryo transfers occurred ( n = 1711) were examined and the Gardner embryo grades on file were converted to NEQsi scores. NEQsi scores ranged from 3 to 11, with a median score of 9. A positive linear relationship existed between the NEQsi scores and the probability of pregnancy (as assessed by quantitative β-HCG). The NEQsi score was a significant predictor of pregnancy ( P < 0.001). Conclusion: Gardner embryo grades can be converted to interval variables and used directly statistical analyses.